Climatic changes and social transformations in the Near East and North Africa during the 'long' 4th millennium BC: A comparative study of environmental and archaeological evidence. (15th March 2016) - Clarke, Joanne; Brooks, Nick; Banning, Edward B.; Bar-Matthews, Miryam; Campbell, Stuart; Clare, Lee; Cremaschi, Mauro; di Lernia, Savino; Drake, Nick; Gallinaro, Marina; Manning, Sturt; Nicoll, Kathleen; et al.
Abstract: This paper explores the possible links between rapid climate change (RCC) and social change in the Near East and surrounding regions (Anatolia, central Syria, southern Israel, Mesopotamia, Cyprus and eastern and central Sahara) during the 'long' 4th millennium (∼4500–3000) BC. Twenty terrestrial and 20 marine climate proxies are used to identify long-term trends in humidity involving transitions from humid to arid conditions and vice versa. The frequency distribution of episodes of relative aridity across these records is calculated for the period 6300–2000 BC, so that the results may be interpreted in the context of the established arid episodes associated with RCC around 6200 and 2200 BC (the 8.2 and 4.2 kyr events). We identify two distinct episodes of heightened aridity in the early-mid 4th, and late 4th millennium BC. These episodes cluster strongly at 3600–3700 and 3100–3300 BC. There is also evidence of localised aridity spikes in the 5th and 6th millennia BC. These results are used as context for the interpretation of regional and local archaeological records with a particular focus on case studies from western Syria, the middle Euphrates, southern Israel and Cyprus. Interpretation of the records involves the construction of plausible narratives of human–climate interaction informed by concepts of adaptation and resilience from the literature on contemporary (i.e. 21st century) climate change and adaptation. The results are presented alongside well-documented examples of climatically-influenced societal change in the central and eastern Sahara, where detailed geomorphological studies of ancient environments have been undertaken in tandem with archaeological research. While the narratives for the Near East and Eastern Mediterranean remain somewhat speculative, the use of resilience and adaptation frameworks allows for a more nuanced treatment of human–climate interactions and recognises the diversity and context-specificity of human responses to climatic and environmental change. Our results demonstrate that there is a need for more local environmental data to be collected 'at source' during archaeological excavations. Highlights: We identify two episodes of aridity ∼3600–3700 and 3100–3300 BC in the Near East. We observe societal change across the region coincident and consistent with RCC. We identify four case studies in the Near East likely to be linked to RCC. We complement these with discussions of RCC in the eastern and central Sahara. We situate our interpretations in resilience and adaptation models.